CONTRIBUTIONS OF WESTERN EDUCATION TO THE MAKING OF MODERN NIGERIA DURING AND AFTER THE FIRST WORLD WAR - M.S, Jayeola-Omoyeni; J.O., Omoyeni (European Scientific Journal, ESJ, 2014)
What is now known as Nigeria consisted of two distinct geographical, cultural and educational divides in the course of state formation, migration and ethnic development. There existed before 1914, the Northern and Southern protectorates of Nigeria and the Colony of Lagos. The Northern protectorate was predominantly dominated by the Hausa, Fulani and Kanuri speaking people, who had for over a thousand years (700- 1914) been wrapped with Islamic religion, Koranic Education and Arabic Literacy, and committed to Muslim and Arabic education, tradition and culture. The north rejected the Christian Missionary form of education when it was introduced to the area in 1845 – Graham (1966). The Southern protectorate was predominantly dominated by the Yoruba and Igbo speaking people, who for many centuries had developed along the indigenous form of traditional education and culture, and who barely seventy two years 1842- 1914 imbibed the European form of education regarded as Formal or “Western Education”. The missionaries established mission schools and people became literates in the Roman script. This scenario was the case of Nigeria before the outbreak of the 1st World War in 1914. This article shows how the likelihood of war prepared Nigerians for a unilateral Amalgamation of the two protectorates without any recourse to war or civil disorder. There was no protest for or against the sudden amalgamation of the protectorates by Lord Frederick Lugard. The article in addition, showcases the impact of amalgamation on the educational development of the country, discusses how the amalgamation led to the acceptance of western form of education hitherto rejected by the Northern Protectorate and analyses the place of Western Education in fostering the making of Nigeria as a modern nation after the 1st world war.